New developments in east-west economic relations - Alexander Predescu (Intereconomics, 1975)
The past four years have witnessed a marked increase in the economic activity between East and West. The volume of foreign trade rose strongly; but as Eastern exports showed only slight increases while their imports from the West went up by leaps and bounds, the deficits of the Comecon countries became ever greater — an imbalance which has given rise to a number of problems.
Keywords: 330; East-West Trade